CERAMIC MATRIX COMPOSITE STRUCTURES WITH CONTROLLED MICROSTRUCTURES FABRICATED USING CHEMICAL VAPOR INFILTRATION (CVI) (2021)
According to a method set forth herein a plurality of preform plies having first and second preform plies can be associated together to define a preform. The preform can be subject to chemical vapor infiltration (CVI) processing to define a ceramic matrix composite (CMC) structure.